Imaginary and social representations of violence and organized crime in Rio Branco (Acre, Brazil) (Delito y Sociedad, 2021)
This paper aims to analyze the social representations of crime and violence in the city of Rio Branco, Acre, Brazil. The research seeks to understand, through interviews and surveys, from the perspective of the Theory of Social Representations, the different views offered by civil servants on organized crime as well as residents' narratives on crime and insecurity, in the context of occupation of the city by criminal organizations. The analysis will focus on: a) mapping the data available on the emergence of criminal organizations in Rio Branco and the social representations of these organizations conveyed by experts; b) analyzing the representations of crime and insecurity of residents in the Belo Jardim neighborhood, described as the most violent, and the Vilage Wilde Maciel neighborhood, officially the least violent, taking into account the number of intentional violent deaths and the dominance of criminal groups; c) discussing whether citizens' feelings of fear of crime and insecurity correspond or change according to the reality of the neighborhood they live in; d) identifying what residents represent as possible changes in their life since the rise of such criminal organizations.
Keywords: Organized crime; social representations; fear of crime and insecurity; violence